Fusion in adolescent idiopathic scoliosis: Anterior, posterior or combined? One-stage or two-stage? Korrekturspondylodesen von adoleszenter idiopathischer Skoliose: Ventral, dorsal, ventrodorsal? Einzeitig oder zweizeitig? - Quack, V.; Rath, Björn; Schenker, H.; Schulze, A.; El Mansy, Y.; Tingart, M.; Betsch, Marcel (Orthopäde, 2015)
Scoliosis is a complex, three-dimensional spinal deformity with various causes. Adolescent idiopathic scoliosis (AIS) is the most common form. Surgical treatment is indicated for curves greater than 45–50° meaured using the Cobb method. We can distinguish among posterior, anterior or combined surgical procedures. Today, the posterior, transpedicular approach has revolutionized scoliosis surgery. This review gives an overview of current surgical options in scoliosis treatment.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Correction; Indication; Operative surgical procedures; Orthopedic fixation devices; Treatment outcome